The Effects of Hormonal Contraception on Physical Performance and Health of Female Athletes: A Systematic Review - Szwech , Julia; Blecharz, Gabriela; Jańczyk, Natalia; Jankowska, Marlena; Mędrysa, Karolina; Presak, Michał; Pokrzepa, Jakub Jan; Baran, Karolina; Winkowska, Alicja; Bartnik, Katarzyna (Quality in Sport, 2025)
Introduction Physical performance and health of female athletes are influenced by physiological changes from the menstrual cycle and hormonal contraception (HC). Hormonal fluctuations can affect muscle strength, endurance, regeneration, and psychological well-being, impacting sports results. HC prevents pregnancy, regulates menstrual cycles and alleviates premenstrual syndrome symptoms. However, it can also cause side effects such as nausea, headaches, weight gain, and mood swings. Aim of the study The aim of the study was to analyze the effects of hormonal contraception on the physical performance and health of female athletes. Materials and methods The article was created based on the PubMed and Cochrane databases. The literature was analyzed using following keywords: hormonal contraception, menstrual cycle, athletes, sex hormones, physical performance Results HC stabilizes hormone levels, potentially reducing performance fluctuations associated with the menstrual cycle. Some studies indicate a slight reduction in aerobic capacity and muscle strength in women using HC, compared to those with a natural cycle. In addition, HC has a positive effect on regeneration after intense training and reducing the risk of overtraining. Athletes reported better sleep quality and fewer cycle-related symptoms, allowing them to train more regularly. What is more, some research highlights estrogen’s anti-inflammatory effect, which supports muscle repair. Conclusion The use of HC use appears to have a minor impact on physical performance, especially among team athletes. However, subjective benefits may improve training comfort. Further research is needed to explore HC’s effects across various sports disciplines.